Influence of Al-Cu doping on the efficiency of BiFeO3 based perovskite solar cell (PSC). (2021) - Kumar, A. Muthu; Peter, I. John; Ramachandran, K.; Mayandi, J.; Jayakumar, K.
Abstract: BiFeO3 (BFO), a multiferroic perovskite in nano form, is used as a photoanode for dye sensitized solar cell along with an electron transporting layer/phosphor, which is rarely reported in literature. Here Al and Cu doped ZnO (AZO & CZO) nanoparticles are composited with bismuth ferrite as this can reduce the density of electron traps and increase the conductivity of the electron transport layer (ETL) of PSCs. The power conversion efficiency (PCE) here is 0.13% but still there are other methods to enhance the PCE, as AZO, CZO is a phosphor as well as an ETL.